Stability Assessment of Landslides in Dahuaqiao Reservoir Area Based on Back Analysis of Slope Monitoring - Yu-xiao Wang; Yu-jie Wang; Long Jiang; Ping Sun; Xingchao Lin; Shouyi Li (Advances in Civil Engineering)
Dahuaqiao Hydropower Station is the sixth cascade hydropower project on the upper stream of the Lancang River, and a number of slope instabilities were found in the reservoir area before reservoir impoundment. The reservoir impoundment and fluctuation of the reservoir water level generally reactivate these potential slope failures or trigger new ones. Therefore, how to cope with the influence of these slope failures on dam safety has always been the focus of attention. However, it is unwise to stabilize all these potentially instable slopes by remedial measures. Based on a two-parameter and four-level back analysis method proposed in this paper, reasonable measures for landslide management are suggested on the basis of the in situ monitoring results and back analysis of geomaterial strength parameters.